Проблеми структурування проектної документації з питань містобудування - Лісіна, Світлана; Мельник, Наталія (Видавництво Львівської політехніки, 2012)
Relevance of the theme explored is that the public authorities, is clearly preparing to host the European Football Championship 2012, which requires a number of documents for construction and rehabilitation of many objects of capital construction – namely, thedensign documentation. The study is to provide urban development operation systemdesign documentation in govemment.
Keywords: будівництво; містобудівна діяльність; оперативний доступ; проектна документація; система пошуку